Motivasi Pekerja Terhadap Penggunaan Alat Pelindung Diri (APD) Pada Proyek Gedung Apartemen The Umalas Signature - Aulya, Zanzabila (PT. Alahyan Publisher Sukabumi, 2024)
Based on BPJS Employment data, there were 153,044 work accidents in 2020. Of this number, 68.5 percent occurred in the environment where work was carried out. Providing and using personal protective equipment (PPE) is an effort to improve occupational safety and health. Work experience and behavior in choosing the type of PPE influence the fulfillment of PPE use. Based on the findings of a preliminary survey conducted on 19 August 2022, through interviews with contractor staff at The Umalas Signature Project which oversees K3, no worker training on K3 was ever provided during the approximately five months the project was operational even though workers are the party most to blame for most work accidents. negligent building practices and negligent use of personal protective equipment. Employees' use of personal protective equipment can be influenced by three elements, namely psychological, individual, and organizational aspects. A total of 39 respondents were surveyed and interviewed to collect data, which was then evaluated using scoring analysis and quantitative descriptive data analysis techniques. To measure the level of motivation of workers in using personal protective equipment (PPE) based on individual, psychological and organizational factors, data analysis was carried out to identify influential factors that influence this behavior. Based on research findings, the organizational factors in the FO 3 statement item which has an average score of 4.5 (very strong) and a percentage value of 95% is a determining factor that influences employee health to use personal safety equipment (PPE). The Individual Factor then displays an influence value of 44.4% based on the multiple linear regression analysis test. The value of the influence of psychological elements is 41.4%. The influence value of organizational factors is 67.1%.